Brick Lane Patchwork (Altre Modernità, 2009)
The essay Brick Lane Patchwork takes its roots in the consideration that the most effective cultural representations of London Brick Lane are explicitly or implicitly linked to the nature of a patchwork. Many contemporary cultural representations made a vain and ambitious effort to portray the real soul(s) of Brick Lane, without taking into consideration its complexity and, therefore, delivering a distinctive image of the area as if it was a single piece of cloth, not a whole quilt. Starting from already existing cultural representations of Brick Lane (Monica Ali's first novel Brick Lane and its filmic adaptation directed by Sarah Gavron, the poetic memoir Salaam Brick Lane - a Year in the New East End and the short film Brick Lane by Paul Makkar, which are going to be privileged squared cloths to be sewn in the above mentioned patchwork), the aim of this essay is both to detect its proper cultural representations and to sew an imaginative patchwork quilt, a new and multiple image of this London area enhancing its hybrid soul(s), its blending procedure and contemporary facets. Ali M., 2004, Brick Lane, Doubleday Black Swan, London.Gavron S., 2007, Brick Lane, Sony Pictures Classics.Hall T., 2005, Salaam Brick Lane - A Year in the New East End, John Murray Publishers, London. Makkar P., 2002, Brick Lane, Anapurna Films.
Keywords: London; Brick Lane; London East End; Patchwork